2009
DOI: 10.1186/1476-5918-8-3
|View full text |Cite
|
Sign up to set email alerts
|

A portable system for collecting anatomical joint angles during stair ascent: a comparison with an optical tracking device

Abstract: Background: Assessments of stair climbing in real-life situations using an optical tracking system are lacking, as it is difficult to adapt the system for use in and around full flights of stairs. Alternatively, a portable system that consists of inertial measurement units (IMUs) can be used to collect anatomical joint angles during stair ascent. The purpose of this study was to compare the anatomical joint angles obtained by IMUs to those calculated from position data of an optical tracking device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 26 publications
(31 reference statements)
7
49
1
Order By: Relevance
“…Alternative means for acquiring temporal, spatial, kinematic, and kinetic data may offer the means to assess this possibility. Portable systems that consist of sensors for tracking body movement in the free-living environment are now available and may be used to collect gait mechanics outcomes [160][161]. The use of such systems in conjunction with traditional laboratory-based equipment may allow for the assessment of function as well as activity and/or participation [162], enhancing our understanding of how prosthetic interventions are used across a variety of environmental conditions.…”
Section: Gait Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative means for acquiring temporal, spatial, kinematic, and kinetic data may offer the means to assess this possibility. Portable systems that consist of sensors for tracking body movement in the free-living environment are now available and may be used to collect gait mechanics outcomes [160][161]. The use of such systems in conjunction with traditional laboratory-based equipment may allow for the assessment of function as well as activity and/or participation [162], enhancing our understanding of how prosthetic interventions are used across a variety of environmental conditions.…”
Section: Gait Mechanicsmentioning
confidence: 99%
“…Although traditional biomechanists may have access to motion analysis laboratories, few may have the space to establish obstacle courses or include stairs and inclines within the available capture volume. Perhaps with the advancement of portable instrumentation systems [160][161], evaluation of environmental barriers in a user's natural environment may be possible. As an alternative, investigators may consider incorporating less sophisticated measures of environmental obstacle negotiation, such as timed stair tests [177] or standardized obstacle courses [178][179], into study protocols as a way to measure these activities.…”
Section: Environmental Obstacle Negotiationmentioning
confidence: 99%
“…Another limitation is that parts of both horse and rider's bodies may be hidden from view, restricting the analysis that can be accurately performed (Greve & Dyson 2012). Bergmann, Mayagoitia, and Smith (2009) reported that body-worn, inertial motion sensors are a practical, non-constraining alternative to optical motion analysis for the measurement of lower-extremity joint angles. Ease of setup and portability makes them suitable for use by clinicians and researchers outside the laboratory environment.…”
Section: Introductionmentioning
confidence: 99%
“…Sensor drift was negligible over the short duration of each trial. Bergmann et al [23] showed that mean motion sensor orientation measurements were strongly correlated with joint angle measurements from an optical tracking device (correlation range: 0.93-0.99, maximum joint ranges of motion: 49°-92°), and we verified the angle measurement accuracy using an inclinometer; in addition, we verified the accuracy of the motion sensor during the rise against a video recording of a single subject.…”
Section: Test Bed Data Collectionmentioning
confidence: 82%